Atorvastatin Reduces the Survival of Candida albicans-Infected BALB/c Mice - Rahal, Elias A.; Constantin, Wissam N.; Zeidan, Nabil; Abdelnoor, Alexander M. (Frontiers in Microbiology, 2015)
Several antimicrobial and immunosuppressive effects have been attributed to the statins class of antihyperlipidemia drugs. Several studies have also indicated clinical benefits for the use of statins during the management of infections and sepsis. To assess whether the immunosuppressive effects of statins outweigh their antimicrobial effects during a fungal infection BALB/c mice were administered Candida albicans via intraperitoneal injection. These mice received either a co-injection of atorvastatin along with the infection, were treated with one injection of atorvastatin per day for five days prior to infection, or were infected and then treated with one injection of atorvastatin for five days afterwards. Groups that received C. albicans without being treated with atorvastatin were included as controls along with a group that only received phosphate-buffered saline. Mouse survival was then monitored; additionally, serum IFN-γ and IL-4 levels were determined by enzyme linked immunosorbent assay (ELISA) to assess pro-inflammatory and pro-humoral responses, respectively. Atorvastatin administration was capable of altering mouse survival rate with the lowest rate (11.1%) being observed in the group treated for five days prior to infection with atorvastatin compared to mice infected but not treated with atorvastatin (44.4%). IFN-γ and IL-4 levels were depressed in all C. albicans-infected groups treated with atorvastatin. The possibility that statin administration may suppress or modulate particular components of the immune system during an infection in man should be further explored in large randomized controlled trials.